2021
DOI: 10.3390/ijms222212243
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2, Cardiovascular Diseases, and Noncoding RNAs: A Connected Triad

Abstract: Coronavirus Disease 2019 (COVID-19), caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), is characterized by important respiratory impairments frequently associated with severe cardiovascular damages. Moreover, patients with pre-existing comorbidity for cardiovascular diseases (CVD) often present a dramatic increase in inflammatory cytokines release, which increases the severity and adverse outcomes of the infection and, finally, mortality risk. Despite this evident association at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 127 publications
0
9
0
1
Order By: Relevance
“…COPD: Chronic obstructive pulmonary disease; Covid-19: Coronavirus disease 19; CT: computed tomography; CTA: Computed tomography angiography; F: female; HTN: hypertension; M: male; NR: not reported; POST-COVID: observed after the COVID-19 infection; not reported in past medical history before COVID-19 infection; R: right; RT-PCR: Reverse transcription polymerase chain reaction for COVID-19 detection; TEE: transesophageal echocardiography; Test +: positive test results; TTE: transthoracic echocardiography. Country Age Sex Clinical manifestation Comorbidities COVID-19 Timing of dissection Dissection Diagnostic method Dissection type (Stanford/Debakey) Extension of dissection Surgical treatment Basheer et al 2 USA 17 M Acute-onset substernal chest pain; COVID-19; Tested positive (test not specified) 14 days after covid test + CTA Stanford Type A; From sinotubular junction to proximal aortic arch Single side branch graft (Gelweave-30mm) Marfan-syndrome Debakey type I Engin et al 8 Turkey 62 M Chest pain radiating to back; COVID-19; Tested positive (test not specified) 20 days after covid symptoms CT Stanford type A; from Aortotomy; AF; DM; lower extremity deep venous insufficiency Debakey type I ascending aorta to iliac bifurcation poly-tetrafluoroethylene tube graft replacement (30mm) Fesharaki et al 11 Iran 43 M …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD: Chronic obstructive pulmonary disease; Covid-19: Coronavirus disease 19; CT: computed tomography; CTA: Computed tomography angiography; F: female; HTN: hypertension; M: male; NR: not reported; POST-COVID: observed after the COVID-19 infection; not reported in past medical history before COVID-19 infection; R: right; RT-PCR: Reverse transcription polymerase chain reaction for COVID-19 detection; TEE: transesophageal echocardiography; Test +: positive test results; TTE: transthoracic echocardiography. Country Age Sex Clinical manifestation Comorbidities COVID-19 Timing of dissection Dissection Diagnostic method Dissection type (Stanford/Debakey) Extension of dissection Surgical treatment Basheer et al 2 USA 17 M Acute-onset substernal chest pain; COVID-19; Tested positive (test not specified) 14 days after covid test + CTA Stanford Type A; From sinotubular junction to proximal aortic arch Single side branch graft (Gelweave-30mm) Marfan-syndrome Debakey type I Engin et al 8 Turkey 62 M Chest pain radiating to back; COVID-19; Tested positive (test not specified) 20 days after covid symptoms CT Stanford type A; from Aortotomy; AF; DM; lower extremity deep venous insufficiency Debakey type I ascending aorta to iliac bifurcation poly-tetrafluoroethylene tube graft replacement (30mm) Fesharaki et al 11 Iran 43 M …”
Section: Resultsmentioning
confidence: 99%
“…Since 11th March 2020, the outbreak of severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) has been declared as a pandemic disease, causing numerous morbidities and mortalities worldwide. 1 , 2 Although Coronavirus disease 19 (Covid-19) had been Initially known as an acute respiratory distress syndrome, more recently it appeared to affect various organs and organ systems, including cardiovascular, gastrointestinal, renal, coagulation, and skin disorders; Most of which related to the hyper-inflammatory state in Covid-19. 3 , 4 Multiple findings imply that the inflammatory state in Covid-19 patients is similar to strong inflammatory syndrome; both of which showing abnormal platelet count, increase in D-dimer, increase in Von Willebrand Factor (VWF), endothelialitis, and pro-inflammatory cytokines activation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to D-dimer, other markers predicting poor prognosis include lymphocytopenia [ 59 , 60 ], thrombocytopenia [ 59 , 60 ], elevated C-reactive protein [ 61 , 62 ], elevated IL-6 [ 60 , 61 , 62 ], elevated lactate dehydrogenase (LDH) [ 63 ], elevated ferritin [ 60 ], sphingolipid profile [ 64 ], increases in soluble tumor necrosis factor or its receptor, or an increase in a disintegrin and metalloproteinase 17 (ADAM17) [ 65 ]. Other risk factors for severe disease and death include advanced age [ 48 ], obesity [ 66 ], vitamin D deficiency [ 67 ], zinc deficiency [ 68 ], and coexisting cardiovascular disease [ 69 ]. Combinations of these factors may thus contribute to more accurate assessment of prognosis.…”
Section: Covid-19-associated Coagulopathymentioning
confidence: 99%
“…Apart from histone modifications and DNA methylation, non-coding RNA (nc-RNA) is an important contributor of epigenetic changes. In COVID-19, several nc-RNA are upregulated or downregulated which render them as potential biomarkers of the disease [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Askari et al reported that several long nc-RNAs and micro RNAs (mi-RNAs) are differentially expressed in COVID-19, some with specific observations in female versus male patients [ 46 ].…”
Section: Altered Epigenomic Signature Of Dna Methylation In Heart Imp...mentioning
confidence: 99%